Correlation between bulk and precipitate composition in Al-Zn-Mg-Cu alloys. (1st February 2022) - Zou, Yan; Wu, Xiaodong; Tang, Songbai; Zhu, Qianqian; Song, Hui; Guo, Mingxing; Cao, Lingfei
ABSTRACT: The composition of precipitates in peak-aged Al-Zn-Mg-Cu alloys with various Zn/Mg ratios has been investigated by atom probe tomography (APT). The results show that the η′ and the T′ phases have different compositions with a similar Zn/Mg ratio in the same alloy. The Zn/Mg ratio within precipitates was shown to be positively correlated with the Zn/Mg ratio in the alloy. Moreover, the size dependency of composition for ageing precipitates in Al-Zn-Mg-Cu alloys has been determined. This study enriches the understanding of precipitate composition relative to that of the bulk in Al-Zn-Mg-Cu alloys.